Development of Real-Time PCR-Based System that Detects Kinetoplast DNA for Diagnosis of Leishmania Infections - Doğantürk, Yağmur Eylül; Kuşkucu, Mert Ahmet; Hökelek, Murat; Bahar-Tokman, Hrisi (Cerrahpaşa Medical Journal, 2022)
Objective: The aim of the study was to develop a real-time polymerase chain reaction-based system that is simple, rapid, and sensitive enough for the diagnosis of Leishmania infections by targeting kinetoplast DNA amplification. Methods: In the study, a standard Leishmania tropica strain was obtained from the Republic of Turkey Ministry of Health Microbiology Reference Laboratory Culture Collection. The parasites were cultivated in a medium. Kinetoplast DNA sequences of Leishmania tropica and kinetoplast DNA sequences representing Leishmania major, Leishmania Infantum, and Leishmania donovani species were downloaded from GenBank and were aligned with the SeqMan program in DNAStar. The highest overlapping kDNA sequences were detected with BioEdit program and pan-primers were designed targeting relevant sequences. The assays were performed in three separate days as triplicates and melting curve analysis was performed for each Leishmania tropica dilutions. Kinetoplast DNA real-time polymerase chain reaction results were compared with the same method detecting Leishmania tropica genomic DNA. Results: The lower detection limit of the developed test was found to be 10° parasite/100 μL and for all groups of dilutions, and intertest coefficient of variation value and regression value (R2) were 0.98 and 0.9589, respectively. The melting temperature was 79° for all Leishmania tropica dilutions. Conclusion: The developed protocol can be used as an alternative tool for quantitative detection of Leishmania species. It is also a useful test to obtain quantitative and accurate results to be used in future studies because of its simplicity, rapidness, sensitivity, and the ease of adaptation to any laboratory setting. Cite this article as: Doğantürk YE, Kuşkucu MA, Hökelek M, Bahar-Tokman H. Development of real-time PCR-based system that detects kinetoplast DNA for diagnosis of leishmania infections. Cerrahpaşa Med J. 2022;46(2):138-143.